DEVELOPMENT OF STUDENT WORKSHEETS ON BUFFER SOLUTION BASED ON GUIDED INQUIRY LEARNING INTEGRATED ETHNOSCIENCE PHASE F OF SENIOR HIGH SCHOOL - Al Muhania, Al Muhania; Andromeda, Andromeda (Chimica Didactica Acta, 2024)
This research aims to develop an ethnoscience-integrated guided inquiry learning-based student worksheet on buffer solution material for class XI SMA/MA students. The development of learner worksheets is carried out using the type of educational design research (EDR) with the Plomp development model, which consists of several stages: preliminary research, product development, and assessment. The validation results by experts show that the developed student worksheets have an average Aiken's V value of 0.92, which is included in the valid category. In addition, the practical test results showed the practicality of the student Worksheets of 96% of teachers and 92% of students, with an average practicality of 94%, classified in the highly practical category. Based on the results of this study, the worksheet for students based on Guided Inquiry Learning integrated with ethnoscience can be declared valid and very practical to be used in learning buffer solutions at grade 11 Senior High Schools.